PENERAPAN MEDIA MANIPULATIF SISTEM PENCERNAAN MANUSIA PADA PEMBELAJARAN IPAS KELAS V DI SDN 098 PIDOLI - Rahmadani, Rahmadani; Suryani Siregar, Irma; Meita Puteri Siregar, Ayu (Jurnal Ilmu Pendidikan Islam, 2026)
This study aims to determine students’ learning outcomes before and after the implementation of manipulative media in the topic of the human digestive system in IPAS learning at SDN 098 Pidoli. The research employed a Classroom Action Research (CAR) method conducted in two cycles with 29 students as subjects. Data were collected through observation, tests, and documentation. The results showed that the use of manipulative media had a positive impact on improving students’ learning outcomes and understanding. Before the implementation, the average score was only 55.96 with 30% mastery. After applying the media, the average score increased to 70 with 49% mastery in Cycle I, and to 81 with 86% mastery in Cycle II. Learning activities became more active through explanations, discussions, hands-on practice, and evaluation. Therefore, manipulative media proved effective in enhancing students’ understanding of the abstract concept of the human digestive system.